Replication in Human Intestinal Enteroids of Infectious Norovirus from Vomit Samples - Hagbom, Marie (Emerg Infect Dis, 2021)
A typical clinical symptom of human norovirus infection is projectile vomiting. Although norovirus RNA and viral particles have been detected in vomitus, infectivity has not yet been reported. We detected replication-competent norovirus in 25% of vomit samples with a 13-fold to 714-fold increase in genomic equivalents, confirming infectious norovirus.